Misvaluation and the corporate propensity to hold cash - Chen, Hsuan-Chi; Chou, Robin K.; Lu, Chien-Lin (Journal of Corporate Finance, 2021)
This study adopts a new perspective, misvaluation, to explain corporate propensity to hold cash. We find a strong cross-sectional relationship between misvaluation and the propensity to hold cash, which can be attributed to firms' investment, cash dividends, and equity raising activities. We further show that the equity issuance channel is driven by both firm-initiated issuance activities and the exercise of employee stock options. The results are robust after controlling for endogeneity issues. Several additional robustness tests reject alternative explanations, such as precautionary motives, agency conflicts, near-term cash needs, and tax motives.